(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to improve students’ learning outcomes in the traditional Indonesian game bola kasti by implementing the Team Games Tournament (TGT) cooperative learning model. The research employed a classroom action research (CAR) design conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. The participants were 24 fourth-grade students at SDN 14 Merapi Timur, consisting of 13 boys and 11 girls. Data were collected through performance tests and observation sheets, while analysis was carried out using comparative descriptive methods. The results revealed a marked improvement in students’ mastery of bola kasti skills, with learning completeness increasing from 37.5% in the pre-cycle to 75% in cycle I and ultimately reaching 100% in cycle II. These findings suggest that the TGT cooperative learning model is an effective instructional strategy for enhancing both technical proficiency and cooperative learning in traditional games. The implications highlight the potential of integrating cooperative learning approaches into physical education to foster skill development and social interaction among elementary school students. The study is supported by references to cooperative learning theory, includes two tables summarizing progress across cycles, and provides observation instruments as supplementary material.